Collective Participation of Water Users in Irrigation Management: A Case From Nepal - S. Khadka, Shyam (1992)
The study examines the factors associated with the process of collective participation among the members of the water users group (WUG)in irrigation management in one of the government·managed irrigation projects in Nepal. Two hundred randomly selected respondents from 40 WUGs were interviewed on a pre-tested schedule. Additional insights and data were derived from official records, direct observation, informal interviews with officials and key informant farmers. Level of participation among the members of the WUGs as measured by their involvement in group decision making in four major tasks of irrigation management and actual resource committed (labour, cash and material) for the maintenance of tertiary structures were found to be relatively low. It was found that the way the WUGS had been structured and its existing leadership pattern could in part be attributable to this state-of-affair. Three sets of factors namely situational, structural and interaction process were included and their relationships with the level of participation in irrigation management examined in the study. The findings of the study indicate that while each of the three groups of factors has its own merit in explaining the process of collective participation in irrigation management, there was greater explanatory power when all three sets of factors were combined and their relationships examined.